Inter-fractional variations in the dosimetric parameters of accelerated partial breast irradiation using a strut-adjusted volume implant. (28th October 2019) - Iijima, Kotaro; Okamoto, Hiroyuki; Takahashi, Kana; Aikawa, Ako; Wakita, Akihisa; Nakamura, Satoshi; Nishioka, Shie; Harada, Ken; Notake, Ryoichi; Sugawara, Akimoto; Yoshimura, Ryoichi; Kunieda, Etsuo; et al.
Abstract: The aim of the study was to evaluate inter-fractional dosimetric variations for high-dose rate breast brachytherapy using a strut-adjusted volume implant (SAVI). For the nine patients included, dosimetric constraints for treatment were as follows: for the planning target volume for evaluation (PTV_Eval), the volume receiving 90, 150 and 200% of the prescribed dose ( V 90%, 150%, 200% ) should be >90%, ≤50 cm 3 and ≤20 cm 3, respectively; the dose covering 1 cm 3 ( D 1cc ) of the organs at risk should be ≤110% of the prescribed dose; and the air volume should be ≤10% of PTV_Eval. Differences in V 90%, 150%, 200%, D 1cc and air volume ($Δ V$ and $Δ D$ ) as inter-fractional dosimetric variations and SAVI displacements were measured with pretreatment and planning computed tomography (CT) images. Inter-fractional dosimetric variations were analyzed for correlations with the SAVI displacements. The patients were divided into two groups based on the distance of the SAVI from the surface skin to assess the relationship between the insertion position of the SAVI and dosimetric parameters. The median Δ V 90%, 150%, 200% for the PTV_Eval in all patients was −0.3%, 0.2 cm 3 and 0.2 cm 3, respectively. The median (range) Δ D 1cc for the chest wall and surface skin was −0.8% (−18.9 to 9.4%) and 0.3% (−7.6 to 5.3%), respectively. SAVI displacement did not correlate with inter-fractional dosimetric variations. In conclusion, the dose constraints were satisfied in most cases. However, there were inter-fractional dosimetric changes due to SAVI displacement.